PENGARUH TERAPI RENDAM KAKI HANGAT TERHADAP TINGKAT KECEMASAN IBU HAMIL TRIMESTER III DI DESA KANDANGTEPUS KECAMATAN SENDURO KABUPATEN LUMAJANG - Arista Fiorentin; Farianingsih Farianingsih; Homsiatur Rohmah (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
Anxiety is a feeling of worry which is a response to internal or external stimuli that can have behavioral, emotional, cognitive and physical symptoms. Anxiety conditions are considered normal when appropriate to the situation and can disappear when the situation has been. This study uses a quasi-experimental type of research with a pretest-posttest approach with control group design, because this study provides interventions to more than one group with different forms of intervention. This study used an experimental group and a control group. The sample in this study were 36 third trimester pregnant women who were taken by purposive sampling technique. Data collection includes coding, editing, entry and cleaning, then the data is analyzed using SPSS. In the treatment group after being given warm foot soak therapy, 94% of mothers experienced mild anxiety and 6% of mothers experienced moderate anxiety, while in the control group 78% of mothers experienced mild anxiety and 22% experienced moderate anxiety. There is a significant difference in the average value of the anxiety level of pregnant women in the third, so Ha is accepted and proves that there is a significant effect on warm foot soak therapy in third trimester pregnant women in Kandangtepus village, Senduro district. Warm foot soak therapy is able to provide a relaxing effect by increasing comfort through a warm sensation on the surface of the soles of the feet. This concept will increase the release of endorphins, so the body feels more relaxed and reduces stress levels. Therefore, soaking the feet in warm water can reduce the anxiety level of pregnant women in the third trimester.